2013
DOI: 10.5732/cjc.013.10148
|View full text |Cite
|
Sign up to set email alerts
|

Locoregional radiotherapy in patients with distant metastases of nasopharyngeal carcinoma at diagnosis

Abstract: Systemic chemotherapy is the basic palliative treatment for metastatic nasopharyngeal carcinoma (NPC); however, it is not known whether locoregional radiotherapy targeting the primary tumor and regional lymph nodes affects the survival of patients with metastatic NPC. Therefore, we aimed to retrospectively evaluate the benefits of locoregional radiotherapy. A total of 408 patients with metastatic NPC were included in this study. The mortality risks of the patients undergoing supportive treatment and those unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
103
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(112 citation statements)
references
References 30 publications
7
103
2
Order By: Relevance
“…However, it is noteworthy that no patient achieved complete remission of the primary tumor after systemic chemotherapy, which underlines the limitation of chemotherapy in eradicating the primary bulky disease. Furthermore, consistent with several previous reports [9,11], increasing the number of cycles of chemotherapy did not seem to improve patients' survival in our cohort. No significant survival benefit was observed for the patients receiving at least four cycles of chemotherapy versus those receiving \4 cycles, raising the possibility of acquired chemoresistance with the increase of chemotherapy cycles.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, it is noteworthy that no patient achieved complete remission of the primary tumor after systemic chemotherapy, which underlines the limitation of chemotherapy in eradicating the primary bulky disease. Furthermore, consistent with several previous reports [9,11], increasing the number of cycles of chemotherapy did not seem to improve patients' survival in our cohort. No significant survival benefit was observed for the patients receiving at least four cycles of chemotherapy versus those receiving \4 cycles, raising the possibility of acquired chemoresistance with the increase of chemotherapy cycles.…”
Section: Discussionsupporting
confidence: 93%
“…Investigators of another retrospective review of 234 patients reported that locoregional radiotherapy significantly extended patients' overall survival when combined with chemotherapy versus chemotherapy alone (3yOS 48.3 vs. 12.4 %, P = 0.001), and the survival benefit was particularly prominent for patients who achieved CR or PR of metastatic lesions after systemic chemotherapy [10]. Similar results were also obtained in a third study which retrospectively evaluated the impact of different treatment strategies on patients' survival [11]. Statistical analysis showed that patients' mortality risk in the group undergoing systemic chemotherapy alone was 130 % higher than that of the group undergoing both systemic chemotherapy and locoregional radiotherapy (P \ 0.001).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…1 NPC has the highest rate of metastasis among head and neck cancers, and distant metastasis is the main cause of treatment failure. 2 NPC is consistently correlated with EBV infection; the expression of neo-viral antigens in tumor cells induces numerous immune cells, referred to as tumor-infiltrating leukocytes, which are attracted to tumor tissues. 3,4 Most studies of the mechanisms of cancer-related inflammation have focused on cancer initiation; in fact, inflammatory mediators and cells are also involved in the migration, invasion and metastasis of malignant cells.…”
Section: Cox-2 Promotes Metastasis In Nasopharyngeal Carcinoma By Medmentioning
confidence: 99%
“…Secondly, neoadjuvant chemotherapy based on cisplatin could improve local control and survival rate in radiotherapy of locally advanced NPC (Xu et al, 2012;Du et al, 2013;Kong et al, 2014). The radiotherapy of nasopharynx, neck and/ or bone metastases to treat the NPC patients with distant metastases could prolong complete response time and increase the survival rate after systematic chemotherapy (Chen et al, 2013;Agnese et al, 2014). Thirdly, NPC was sensitive to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%